PD-L1 as a Potential Therapeutic Target to Immune Checkpoint Blockade in Cervical Cancer: A Review of the Literature - Lubis, Humairah Medina Liza; Sitompul, Asma Dwi Nantika; Shaik Hussain, Basrah Bee Binte; Nasution, Annissa Ambaravista (Universitas Muhammadiyah Sumatera Utara, 2022)
Cervical cancer (CC) is still one of the most common malignant tumors in women worldwide. Malignant tumors are known for evading immune surveillance. In cervical lesions, the mechanism has received less attention. Evasion of immune surveillance through a variety of mechanisms; one of which is the immune checkpoint pathway has attracted interest because it can be therapeutically targeted, the programmed cell death 1 (PD-1) pathway that tumor cells use to block antitumoral immune responses. Increasing the prevalence of PD-L1 expression in up to 80% of cervical malignancies, there is a significant indication using immunotherapy to maintain the immune response against malignancies. The purpose of this literature review is to examine the potential role of immune checkpoint inhibitors in the treatment of cervical neoplastic lesions, by reviewing articles on cervical intraepithelial neoplasia (CIN) and cervical cancer that carried out histopathological and immunohistochemical examination PD-L1 as well as immunotherapy treatment with anti-PD-L1. There were 10 articles were found to be associated with anti-PD-1/PD-L1 immunotherapy. In conclusion, PD-L1 is a potential therapeutic target in cervical cancer